SMEs Business Assistance through Digital Marketing: International Service Collaboration - Riskin Hidayat; Syamsul Hadi; Ambar Lukitaningsih; Muinah Fadhilah; Eko Agus Setiawan; Intan Puspita Sari; Nguyen Le Thanh Danh; Le Ngoc Minh Khoi (IMPACTS: International Journal of Empowerment and Community Services, 2026)
Purpose – This community service aims to address the challenges SMEs face in the global market, specifically limited digital knowledge and infrastructure, by enhancing digital literacy through international collaboration. Methods – The program involved a partnership between MM students from Universitas Sarjanawiyata Tamansiswa and international students to provide intensive training and hands-on support. Activities focused on digital marketing basics, e-commerce platforms, social media marketing, SEO, and direct mentorship in managing websites and running digital campaigns. Result and discussions – The implementation provided SMEs with access to global best practices and the latest technologies. Evaluation showed significant improvements in participants' digital marketing skills and business performance, characterized by increased sales, expanded market reach, and improved operational efficiency. Conclusion – This collaborative model offers a sustainable solution for SME competitiveness, though continuous mentoring and infrastructure support may be required to maintain these technological gains in the long term